Real-World Evaluation of the Effectiveness of Intravitreal Bevacizumab Injection for Neovascular Age-Related Macular Degeneration at Cipto Mangunkusumo National Referral Hospital - Adriono, Gitalisa Andayani; Pambudy, Indra Maharddhika; Victor, Andi Arus; Djatikusumo, Ari; Yudhanta, Anggun Rama; Hutapea, Mario Marbungaran; Triyoga, Ichsan Fauzi (International Journal of Retina, 2025)
Introduction: Neovascular age-related macular degeneration (nAMD) is a leading cause of visual impairment globally. While intravitreal anti-VEGF therapy is the standard treatment, real-world data on bevacizumab (IVB), the most accessible agent in Indonesian public hospitals despite being off-label, remains limited. This study aims to evaluate the effectiveness of IVB in patients with nAMD at a tertiary referral center in Indonesia. Methods: This retrospective study included patients diagnosed with nAMD who received IVB injections at Cipto Mangunkusumo National Referral Hospital between January and December 2017. Inclusion criteria encompassed patients with confirmed nAMD and available clinical data pre- and post-injection. Data on demographics, best-corrected visual acuity (BCVA), central macular thickness (CMT) measured by OCT, and IVB injection regimen were extracted from electronic medical records. Statistical analysis was performed using Wilcoxon signed-rank and Mann–Whitney U tests, with p < 0.05 considered statistically significant. Result: A total of 138 eyes from 131 patients (mean age: 66.7 years; 51% male) were analyzed. The median number of injections was three (range: 1–6). Mean BCVA showed a non-significant improvement from 1.19 to 1.14 logMAR (mean change: 0.05 logMAR; p = 0.770). Subgroup analysis indicated significant improvement in eyes with baseline VA worse than 1.32 logMAR (mean gain: 0.54 logMAR; p < 0.01) and a significant decline in eyes with baseline VA between 0.48 and 1.00 logMAR (mean loss: 0.21 logMAR; p = 0.02). CMT significantly decreased by an average of 108.33 µm (p < 0.01). Conclusion: IVB treatment for nAMD resulted in significant anatomical improvement and was particularly effective in patients with poor baseline visual acuity. These findings highlight the role of IVB in real-world clinical practice within resource-limited settings.